Interpretations of proof-of-life videos and their impact on supported interventions. Issue 2 (4th May 2019) - Craun, Sarah W.; Rossin, Mark J.; Collier, Matthew R.
ABSTRACT: Hostage videos released by terrorist organisations are made not only to establish proof life, but also as a way to influence those who watch them. These videos can be used to find new terrorist recruits, influence negotiators, and scare the public. Over 200 law enforcement officers completed surveys measuring their impressions across four hostage proof of life videos. We measured how these varied impressions may impact support for several interventions options, while also considering their experience working a hostage situation or having crisis negotiation training. The videos were viewed differently in terms of threat level, emotionality and urgency; however, even with different reactions across videos support for various interventions remained stable. For example, paying ransom had very low support regardless of the level of threat, urgency or emotionality reported. Neither previous crisis negotiation training nor working a hostage situation impacted support for various intervention options when controlling for impressions of the videos.